2019
DOI: 10.1111/petr.13495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhospital outcomes of pediatric heart transplantation between single ventricle congenital heart disease and cardiomyopathy

Abstract: Data investigating the impact of household income and other factors on SV patient status‐post‐Fontan palliation after heart transplantation are lacking. We aim to evaluate factors affecting outcomes after OHT in this population. The PHIS database was interrogated for either SV or myocarditis/primary CM who were 4 years or older who underwent a single OHT. There were 1599 patients with a median age of 13.2 years (IQR: 9.3‐16.1). Total hospital costs were significantly higher in the SV group ($408 000 vs $294 00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…90 Individual income/SES Associations between individual SES and post-transplant outcomes varied. Several studies found higher income levels or SES was associated with better health outcomes, including lower risk of postoperative mortality, 52 shorter length of hospitalization, 93 lower risk of rejection or graft failure, 16,52 and lower long-term mortality rates. 52 However, other studies found no differences in likelihood for transplant, 52 post-transplant length of stay, 52 or mortality 86 across SES.…”
Section: Insurancementioning
confidence: 99%
“…90 Individual income/SES Associations between individual SES and post-transplant outcomes varied. Several studies found higher income levels or SES was associated with better health outcomes, including lower risk of postoperative mortality, 52 shorter length of hospitalization, 93 lower risk of rejection or graft failure, 16,52 and lower long-term mortality rates. 52 However, other studies found no differences in likelihood for transplant, 52 post-transplant length of stay, 52 or mortality 86 across SES.…”
Section: Insurancementioning
confidence: 99%
“…For instance, lower‐income families have worse graft survival, while higher family income is linked to improved in‐hospital survival. 53 Black race and Medicaid insurance are also associated with medication nonadherence, which in turn leads to worse transplant outcomes. 54 Factors linked to nonadherence include lower parental education levels, parental psychosocial issues, nonprivate insurance, financial limitations, and family conflicts.…”
Section: Heart Failure/transplantmentioning
confidence: 99%